Improved quantitative 90Y bremsstrahlung SPECT/CT reconstruction with Monte Carlo scatter modeling. Issue 12 (28th October 2017) - Dewaraja, Yuni K.; Chun, Se Young; Srinivasa, Ravi N.; Kaza, Ravi K.; Cuneo, Kyle C.; Majdalany, Bill S.; Novelli, Paula M.; Ljungberg, Michael; Fessler, Jeffrey A.
Abstract : Purpose: In 90 Y microsphere radioembolization (RE), accurate post‐therapy imaging‐based dosimetry is important for establishing absorbed dose versus outcome relationships for developing future treatment planning strategies. Additionally, accurately assessing microsphere distributions is important because of concerns for unexpected activity deposition outside the liver. Quantitative 90 Y imaging by either SPECT or PET is challenging. In 90 Y SPECT model based methods are necessary for scatter correction because energy window‐based methods are not feasible with the continuous bremsstrahlung energy spectrum. The objective of this work was to implement and evaluate a scatter estimation method for accurate 90 Y bremsstrahlung SPECT/CT imaging. Methods: Since a fully Monte Carlo (MC) approach to 90 Y SPECT reconstruction is computationally very demanding, in the present study the scatter estimate generated by a MC simulator was combined with an analytical projector in the 3D OS‐EM reconstruction model. A single window (105 to 195‐keV) was used for both the acquisition and the projector modeling. A liver/lung torso phantom with intrahepatic lesions and low‐uptake extrahepatic objects was imaged to evaluate SPECT/CT reconstruction without and with scatter correction. Clinical application was demonstrated by applying the reconstruction approach to five patients treated with RE to determine lesion and normal liver activity concentrations using a (liver) relative calibration. Results: There was convergence of the scatter estimate after just two updates, greatly reducing computational requirements. In the phantom study, compared with reconstruction without scatter correction, with MC scatter modeling there was substantial improvement in activity recovery in intrahepatic lesions (from > 55% to > 86%), normal liver (from 113% to 104%), and lungs (from 227% to 104%) with only a small degradation in noise (13% vs. 17%). Similarly, with scatter modeling contrast improved substantially both visually and in terms of a detectability index, which was especially relevant for the low uptake extrahepatic objects. The trends observed for the phantom were also seen in the patient studies where lesion activity concentrations and lesion‐to‐liver concentration ratios were lower for SPECT without scatter correction compared with reconstruction with just two MC scatter updates: in eleven lesions the mean uptake was 4.9 vs. 7.1 MBq/mL ( P = 0.0547), the mean normal liver uptake was 1.6 vs. 1.5 MBq/mL ( P = 0.056) and the mean lesion‐to‐liver uptake ratio was 2.7 vs. 4.3 ( P = 0.0402) for reconstruction without and with scatter correction respectively. Conclusions: Quantitative accuracy of 90 Y bremsstrahlung imaging can be substantially improved with MC scatter modeling without significant degradation in image noise or intensive computational requirements.